ANALISIS GEOLOGI STRUKTUR DAN PENGARUHNYA TERHADAP SISTEM HIDROTERMAL DAERAH SAMBOJA km.38, KUTAI KARTANEGARA - .Jamaluddin, Jamaluddin; Kaunang, Imanuel (PETROGAS: Journal of Energy and Technology, 2025)
This study analyzes the influence of geological structures on the hydrothermal system in the Samboja km.38 area, Kutai Kartanegara, based on geochemistry and structural geology data. The analysis results show that the pH values range from 6.5 to 7.6, TDS from 502 mg/L to 592 mg/L, and electrical conductivity (EC) from 1005 mS/cm to 1084 mS/cm. The hot water temperature ranges from 37.1°C to 39°C indicating hydrothermal activity. The geological structure analysis reveals the presence of shear joints with dominant NW-SE and NE-SW orientations, serving as migration pathways for hydrothermal fluids. The presence of thrust faults is identified as a key factor controlling the movement of geothermal fluids. These findings indicate that geological structures play a crucial role in determining the distribution and characteristics of the hydrothermal system in the study area.